3
$\begingroup$

Given a triangle $\Delta ABC$ with circumcenter $O$, and incenter $I$.

If $∠ABC = 45°$, $OI = d$, and $c − b = d√2$,

Find the value of $\sin A$.

I've thought of using the fact that $d^2 = R(R-2r)$ where $R$ is the circumradius and $r$ is the inradius. But I didn't know where to apply it.

$\endgroup$
1
  • 2
    $\begingroup$ "Find the possible value of $\sin A$." makes no sense. Do you mean "Find the possible values of $\sin A$." or "Find the value of $\sin A$."? $\endgroup$
    – joriki
    Dec 21, 2012 at 17:11

2 Answers 2

1
$\begingroup$

Seat your belt, it will be great...

You can use your $d^2 = R(R-2r)$, which gives you

$(c-b)^2 = 2d^2 = 2R(R-2r) = 2R^2-4rR$

Then, you remark that the area of the triangle can be obtained with $r$ or with $R$ :

$\displaystyle\text{Area} = \frac{(a+b+c)r}{2}$ and $\displaystyle\text{Area} = \frac{ab\sin{C}}{2} = \frac{abc}{4R}$

So you have $\displaystyle\frac{(a+b+c)r}{2} = \frac{abc}{4R}$, thus $\displaystyle2rR=\frac{abc}{a+b+c}$

Putting it in the first equality gives :

$\displaystyle c^2+b^2-2bc = 2R^2-2\frac{abc}{a+b+c}$

But $\displaystyle \frac{b}{\sin{B}} = 2R$ and $\displaystyle\sin{B} = \frac{\sqrt{2}}{2}$, so $b=\sqrt{2}R$ and

$\displaystyle c^2+b^2-2bc = b^2-2\frac{abc}{a+b+c}$

$\displaystyle\Leftrightarrow c^2 - 2bc = -2\frac{abc}{a+b+c}$

$\displaystyle\Leftrightarrow c - 2b = -2\frac{ab}{a+b+c}$

$\displaystyle\Leftrightarrow (c - 2b)(a+b+c) = -2ab$

$\displaystyle\Leftrightarrow ac+bc+c^2-2ab-2b^2-2bc = -2ab$

$\displaystyle\Leftrightarrow ac+c^2-2b^2-bc = 0$

Now, we can use $a = 2R\sin A$, $b = 2R\sin B$, and $c = 2R\sin C$ to

$\displaystyle \sin A \sin C+\sin^2 C-2\sin^2 B-\sin B \sin C = 0$

$\displaystyle\Leftrightarrow \sin A \sin C+\sin^2 C-1-\frac{\sqrt{2}}{2} \sin C = 0$

We also know that

$\sin C = \sin(180°-45°-A) = \sin 135° \cos A - \sin A \cos 135° = \frac{\sqrt{2}}{2}(\cos A + \sin A)$

Thus,

$\displaystyle \sin A \frac{\sqrt{2}}{2}(\cos A + \sin A)+\frac{1}{2}(\cos A + \sin A)^2-1- \frac{1}{2}(\cos A + \sin A) = 0$

$\displaystyle\Leftrightarrow \sqrt{2} \sin A \cos A + \sqrt{2}\sin^2 A+\cos^2 A + \sin^2 A + 2\sin A \cos A-2- \cos A - \sin A = 0$

$\displaystyle\Leftrightarrow (2+\sqrt{2}) \sin A \cos A + \sqrt{2}\sin^2 A -1 - \cos A - \sin A = 0$

To only have $\sin$, we can isolate $\cos A$ and square terms...

$\sqrt{2}\sin^2 A - \sin A - 1 = \cos A (1 - (2+\sqrt{2}) \sin A)$

$\Rightarrow (\sqrt{2}\sin^2A - \sin A - 1)^2 = \cos^2 A (1 - (2+\sqrt{2}) \sin A))^2$

Let $x = \sin A$ :

$(\sqrt{2}x^2-x-1)^2 = (1-x^2)(1 - (2+\sqrt{2}) x)^2$

$\Leftrightarrow 2x^4+x^2+1-2\sqrt{2}x^3-2\sqrt{2}x^2+2x = (1-x^2)(1 - (4+2\sqrt{2})x + (6+4\sqrt{2})x^2)$

$\Leftrightarrow 2x^4-2\sqrt{2}x^3+(1-2\sqrt{2})x^2+2x+1 = -(6+4\sqrt{2}) x^4 + (4+2\sqrt{2})x^3+(5+4\sqrt{2})x^2 - (4+2\sqrt{2})x + 1$

$\Leftrightarrow (8+4\sqrt{2})x^4-(4+4\sqrt{2})x^3-(4+6\sqrt{2})x^2+(6+2\sqrt{2})x = 0$

A solution is $x = 0$ which is impossible so it gives us :

$(4+2\sqrt{2})x^3-(2+2\sqrt{2})x^2-(2+3\sqrt{2})x+(3+\sqrt{2}) = 0$

Aaaand... I don't want to find the solution, especially since I've probably make a mistake somewhere :D. There surely is something shorter but perhaps It could help you to find a nice solution!

$\endgroup$
1
$\begingroup$

keep going:$\ (4+2\sqrt{2})x^3-(2+2\sqrt{2})x^2-(2+3\sqrt{2})x+(3+\sqrt{2})=4x^3-2\sqrt{2}x^2+2\sqrt{2}x^3-2x^2-3\sqrt{2}x+3-2x+\sqrt{2}=2\sqrt{2}x^2*(\sqrt{2}x-1)+2x^2(\sqrt{2}x-1)-3(\sqrt{2}x-1)-(\sqrt{2})(\sqrt{2}x-1)=(\sqrt{2}x-1)[(2\sqrt{2}+2)x^2-(3+\sqrt{2})]$=0

$\ x=\sqrt{2}/2$ or $\ x^2=(3+\sqrt{2})/(2\sqrt{2}+2)$ ie $\ x=\sqrt{(2\sqrt{2}-1)/2} $

now you can know $\sin A$

$\endgroup$

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .